EFFECTS OF INSTRUMENTAL AND VOCAL MUSIC THERAPY ON BETA-ENDORPHIN RELEASE AND STRESS REDUCTION: A CONTROLLED EXPERIMENTAL STUDY - Ketut sumerjana; I Komang Sudirga; I Kt. Suteja; I Wayan Suharta (International Journal of Social Science, 2025)
Chronic stress is a pervasive global health issue linked to psychological and physiological disorders. Music therapy has emerged as a non-invasive, cost-effective intervention with demonstrated benefits in emotional regulation and neurochemical modulation. Among its proposed mechanisms is the stimulation of beta-endorphin production, a neuropeptide associated with pain relief, mood enhancement, and stress reduction. This study aimed to evaluate the effects of instrumental and vocal music therapy on beta-endorphin hormone levels and subjective stress reduction in adults experiencing moderate to high stress A randomized controlled trial was conducted involving 90 participants aged 18–45 with self-reported stress levels above the clinical threshold. Participants were randomly assigned to three groups: instrumental music therapy, vocal music therapy, or a no-intervention control. Each intervention group received 30-minute music therapy sessions three times per week for four weeks. Serum beta-endorphin levels were measured pre- and post-intervention using ELISA assays. Subjective stress was assessed using the Perceived Stress Scale (PSS). Both instrumental and vocal music therapy groups showed significant increases in beta-endorphin levels compared to the control (p < 0.01), alongside marked reductions in PSS scores (p < 0.001). Vocal therapy demonstrated a slightly higher effect size. Instrumental and vocal music therapy significantly enhance beta-endorphin secretion and reduce perceived stress, suggesting their utility as complementary interventions in stress management protocols.